Ciliopathy Protein Tmem107 Plays Multiple Roles in Craniofacial Development - Cela, P; Hampl, M; Shylo, N A; Christopher, K J; Kavkova, M; Landova, M; Zikmund, T; Weatherbee, S D; Kaiser, J; Buchtova, M (Journal of dental research, 2018)
A broad spectrum of human diseases called ciliopathies is caused by defective primary cilia morphology or signal transduction. The primary cilium is a solitary organelle that responds to mechanical and chemical stimuli from extracellular and intracellular environments. Transmembrane protein 107 (TMEM107) is localized in the primary cilium and is enriched at the transition zone where it acts to regulate protein content of the cilium. Mutations in TMEM107 were previously connected with oral-facial-digital syndrome, Meckel-Gruber syndrome, and Joubert syndrome exhibiting a range of ciliopathic defects. Here, we analyze a role of Tmem107 in craniofacial development with special focus on palate formation, using mouse embryos with a complete knockout of Tmem107. Tmem107-/- mice were affected by a broad spectrum of craniofacial defects, including shorter snout, expansion of the facial midline, cleft lip, extensive exencephaly, and microphthalmia or anophthalmia. External abnormalities were accompanied by defects in skeletal structures, including ossification delay in several membranous bones and enlargement of the nasal septum or defects in vomeronasal cartilage. Alteration in palatal shelves growth resulted in clefting of the secondary palate. Palatal defects were caused by increased mesenchymal proliferation leading to early overgrowth of palatal shelves followed by defects in their horizontalization. Moreover, the expression of epithelial stemness marker SOX2 was altered in the palatal shelves of Tmem107-/- animals, and differences in mesenchymal SOX9 expression demonstrated the enhancement of neural crest migration. Detailed analysis of primary cilia revealed region-specific changes in ciliary morphology accompanied by alteration of acetylated tubulin and IFT88 expression. Moreover, Shh and Gli1 expression was increased in Tmem107-/- animals as shown by in situ hybridization. Thus, TMEM107 is essential for proper head development, and defective TMEM107 function leads to ciliary morphology disruptions in a region-specific manner, which may explain the complex mutant phenotype.
Keywords: defekty neurální trubice; craniofacial anomalies; oral pathology; cilie; Membrane Proteins; Cleft Lip; Palate; growth/development; mineralized tissue/development; Skull; transkripční faktory SOX; Neural Tube Defects; cell signaling; zvířata; myši; Cilia; orofacial clefts; SOX Transcription Factors; Mice; obličejové kosti; myši knockoutované; Craniofacial Abnormalities; Mice, Knockout; maxilofaciální vývoj; kraniofaciální abnormality; Maxillofacial Development; membránové proteiny; rozštěp rtu; Animals; lebka; patro; Facial Bones